Kecenderungan Agresivitas pada Mahasiswa kaitannya dengan konformitas teman sebaya dan Regulasi Emosi - Ristitania, Kinan Ladiva Ristitania; Winta, Mulya Virgonita Iswindari; Amelia, Cristine Roselvia Tri Amelia (Reswara Journal of Psychology, 2023)
This research aims to determine the relationship between peer conformity and emotional regulation with aggressive tendencies in students. The hypothesis proposed in this research is that there is a positive relationship between peer conformity and aggressiveness. The higher the peer conformity score, the higher the aggressiveness, and vice versa and there is a negative relationship between emotional regulation and aggressiveness. The higher the emotional regulation, the lower the aggressiveness, and vice versa. The subjects in this research were 75 students, including 25 students from Diponegoro University, 25 students from Semarang State University, and 25 students from Semarang University. Likewise, the characteristics of student respondents who have been aggressive, aged 18-25 years. The sampling technique used was purposive sampling technique. Research data was collected using three scales, namely the Aggressiveness Scale, Peer Conformity Scale, and Emotion Regulation Scale. Data analysis was carried out using hierarchical correlation analysis. The results of the research show that there is a relationship between peer conformity and emotional regulation and aggressive tendencies with a value of R square = 0.143 and p = 0.004 (p<0.05), so the hypothesis in this study is that there is a relationship between peer conformity and emotional regulation and aggressive tendencies in student.